AuNPs‐HRP microneedle biosensor for ultrasensitive detection of hydrogen peroxide for organ preservation. Issue 2 (29th October 2018) - Narayanan, Jeyaraman S.; Slaughter, Gymama
Abstract: The preservation of tissues and organs for transplantation has garnered considerable attention due to the oxidative stress that arises from the excess of reactive oxygen species produced upon the removal of an organ from its native environment. Herein, gold nanoparticles (AuNPs)‐horseradish peroxidase (HRP) ultrasensitive microneedle biosensor is developed using a simple electrochemical method for the determination of H2 O2 . Tungsten microwire was homogenously modified with AuNPs via electrodeposition and 3‐mercaptopropionic acid (MPA) to form self‐assembled monolayers (SAMs) for the immobilization of HRP. The prepared AuNPs‐MPA electrode exhibited high electrocatalytic activity towards the reduction of H2 O2 . At an applied potential of −300 mV, the AuNPs‐HRP electrode yielded a linear ranges of 5 nM to 5 µM H2 O2 ( R  = 0.999) and 1–5 mM H2 O2 ( R  = 0.985) with a low detection limit of 800 pM and a sensitivity of 490.59 Ma/mM/cm 2 on average as the result of the strong synergistic effect between HRP and AuNPs. Common interfering species such as ascorbic acid, acetaminophen, glucose and uric acid were effectively eliminated. In addition, the fabricated biosensor exhibited high electrocatalytic activity for the determination of H2 O2 in real time from rat abdominal wall perfused with histidine–tryptophan–ketoglutarate solution.